A silicon carbide-based multi-element composite nanowire film and a preparation method and application thereof

By preparing ternary composite nanowire films with silicon dioxide and carbon layers coated on the surface of silicon carbide nanowires or binary composite nanowire films with silicon carbide nanowires inserted inside carbon nanotubes, the problems of surface inertness and poor conductivity of silicon carbide nanowires are solved, and the electromagnetic wave absorption and conductivity of the materials are improved, making them suitable for microwave absorbing materials and supercapacitors.

CN117672591BActive Publication Date: 2026-11-06NORTHWESTERN POLYTECHNICAL UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311605779.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-28
Publication Date
2026-11-06
Estimated Expiration
2043-11-28

AI Technical Summary

Technical Problem

The surface of silicon carbide nanowires is inert and smooth, which is not conducive to the loading of active materials, has poor conductivity, and is not conducive to the rapid transport of electrons.

Method used

The preparation of ternary composite nanowire thin films based on silicon carbide includes coating silicon carbide nanowires with a silicon dioxide layer and coating the silicon dioxide layer with a carbon layer to form a network structure; or preparing binary composite nanowire thin films with silicon carbide nanowires inserted inside carbon nanotubes, and controlling the structure through oxidation treatment and chemical vapor deposition.

Benefits of technology

It improves the conductivity and dielectric loss of the material, achieves impedance matching and interface polarization, and enhances the electromagnetic wave absorption performance. It is suitable for lightweight, high-strength absorbing materials and nano-conductive frameworks for supercapacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117672591B_ABST
    Figure CN117672591B_ABST
Patent Text Reader

Abstract

The application discloses a kind of multi-element composite nanowire films based on silicon carbide and preparation method and application thereof, and relates to nanometer film material technical field.The film includes interwoven or lapped ternary composite nanowires, and the network structure formed;The ternary composite nanowires include silicon carbide nanowires, the silicon dioxide layer coated on the surface of the silicon carbide nanowires and the carbon layer coated on the surface of the silicon dioxide layer.The film material prepared by the application can be used as light weight high strength wave absorbing material, and can also be used for the nanometer conductive framework of super capacitor, and has wide application prospect in electromagnetic absorption and super electric device and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanofilm materials technology, specifically to a silicon carbide-based multi-component composite nanowire thin film, its preparation method, and its applications. Background Technology

[0002] Silicon carbide nanowires (SiC) NWs SiC inherits a series of excellent properties from bulk ceramic materials, such as high melting point, high strength, corrosion resistance, oxidation resistance, and high-temperature stability, while also possessing the large aspect ratio, high specific surface area, and outstanding mechanical properties of one-dimensional materials. Therefore, SiC with a self-supporting structure... NWs The membrane and nanowires intertwine or overlap to form a continuous network structure, which, as a novel lightweight and flexible nanoconductive framework, has broad application prospects in high-performance microwave absorbing materials and supercapacitors.

[0003] However, pure SiC NWs Due to its relatively high real part (ε′) and low imaginary part (ε″) of dielectric constant, SiC exhibits poor impedance matching and poor dielectric properties, limiting its applications. Meanwhile, SiC... NWs The surface is inert and smooth, which is not conducive to the loading of active materials, and the conductivity is not ideal, hindering the rapid transport of electrons. Carbon (C) materials have the characteristics of low density, good chemical stability, high dielectric loss, and excellent conductivity. The introduction of SiC... NWs Films can improve its overall performance. Silica (SiO2), as a microwave-transparent material, has a low complex dielectric constant and can be used as a SiC / C... NWs The heterogeneous interface of the film improves its impedance matching, allowing more electromagnetic waves to enter the absorbing material. Simultaneously, it generates interfacial polarization, increasing dielectric loss and thus improving its microwave loss performance. The material's properties are not only related to its composition but also closely related to its structure. The construction of SiC... NWs Composite materials with SiC should not only give full play to the advantages of SiC. NWs In addition to considering the inherent properties of C materials, structural design is also necessary to further optimize performance. Research has found that eggshell structures (such as Fe3O4@C and Co3Fe7@C) possess large specific surface areas and unique cavity structures. The multi-component and void structures in these structures can improve dielectric loss, adjust impedance matching, reduce electromagnetic wave reflection, and significantly enhance electromagnetic wave attenuation performance. Furthermore, eggshell structures (such as Fe3O4-CeO2@C), due to their unique structural characteristics, can provide richer pathways for rapid electron transport and more reactive sites, making them highly suitable for use as nano-conductive framework materials in supercapacitors. Currently, no nanowire thin film materials with a tube-in-wire structure in SiC@C have been reported. Summary of the Invention

[0004] To address the shortcomings of the aforementioned background technology, the main technical problem solved by this invention is: SiC NWs The surface is inert and smooth, which is not conducive to the loading of active materials, and the conductivity is not ideal, hindering the rapid transport of electrons. This invention provides a silicon carbide-based multi-component composite nanowire thin film, its preparation method, and its applications. The thin film material prepared by this method can be used as a lightweight and high-strength microwave absorbing material, and also as a nano-conductive framework for supercapacitors, showing broad application prospects in electromagnetic absorption and supercapacitor devices.

[0005] The first objective of this invention is to provide a silicon carbide-based ternary composite nanowire thin film, comprising intertwined or overlapping ternary composite nanowires forming a network structure;

[0006] The ternary composite nanowire includes silicon carbide nanowires, a silicon dioxide layer covering the surface of the silicon carbide nanowires, and a carbon layer covering the surface of the silicon dioxide layer.

[0007] Preferably, the diameter of the silicon carbide nanowires is 30-500 nm; the thickness of the silicon dioxide layer is 10-250 nm; and the thickness of the carbon layer is 5-150 nm.

[0008] The second objective of this invention is to provide a silicon carbide-based binary composite nanowire thin film, which is prepared by removing the silicon dioxide layer from the aforementioned silicon carbide-based ternary composite nanowire thin film; the silicon carbide-based binary composite nanowire thin film comprises a network structure formed by intertwined or overlapping binary composite nanowires.

[0009] The binary composite nanowire film includes carbon nanotubes and silicon carbide nanowires inserted within the carbon nanotubes.

[0010] Preferably, the carbon nanotube has a wall thickness of 5-150 nm; the silicon carbide nanowire has a diameter of 30-500 nm; and the gap between the carbon nanotube and the silicon carbide nanowire is 10-250 nm.

[0011] The third objective of this invention is to provide a method for preparing a silicon carbide-based ternary composite nanowire thin film, comprising the following steps:

[0012] Silicon carbide nanowire films were oxidized in air to obtain SiC / SiO2 nanowire films.

[0013] The SiC / SiO2 nanowire film was placed in a deposition furnace, and argon gas was introduced at a rate of 1.5–2.5 L / min. The temperature was increased to 950–1100 °C at a rate of 4–6 °C / min. Then, methane was introduced at a rate of 0.6–1.2 L / min. After holding at this temperature for 5–60 min, a ternary composite nanowire film based on silicon carbide was obtained.

[0014] Preferably, the silicon carbide nanowire thin film is prepared according to the following steps:

[0015] Weigh a certain amount of glucose, silicon dioxide and sodium salt powder, grind them to make them evenly mixed, and then pass them through a 100-mesh sieve. Spread the sieved powder evenly into a graphite crucible.

[0016] A graphite crucible containing the mixed powder is kept at 1400–1700℃ for 1–4 hours under the protection of an inert gas to obtain a silicon carbide nanowire film.

[0017] The molar ratio of glucose, silicon dioxide, and sodium salt is 1:(1.2-4.5):(1.8-5.4).

[0018] The sodium salt includes sodium chloride or sodium fluoride.

[0019] Preferably, the oxidation treatment is to oxidize SiC NWs The film is placed in an air atmosphere and kept at 1000–1200℃ for 0.5–3 hours.

[0020] The fourth objective of this invention is to provide a method for preparing a silicon carbide-based binary composite nanowire thin film, comprising the following steps:

[0021] The ternary composite nanowire film was kept at 1300–1600 °C for 1–4 h under the protection of an inert gas to obtain a silicon carbide-based binary composite nanowire film.

[0022] Among them, when the ternary composite nanowire film is heat-treated under the protection of an inert gas, the cooling rate is 3-5℃ / min.

[0023] The fifth objective of this invention is to provide an application of silicon carbide-based ternary composite nanowire thin films in electromagnetic dissipation and supercapacitors.

[0024] The sixth objective of this invention is to provide an application of silicon carbide-based binary composite nanowire thin films in electromagnetic dissipation and supercapacitors.

[0025] Compared with the prior art, the beneficial effects of the present invention are:

[0026] This invention provides a silicon carbide-based multi-component composite nanowire thin film, its preparation method, and its applications. The ternary composite nanowire thin film (SiC / SiO2 / C ternary composite nanowire thin film) prepared by this invention exhibits a microstructure at the SiO2 interface that can be controlled by adjusting the oxidation time and temperature, ensuring the uniformity of the SiO2 layer. The outer shell C layer is prepared by chemical vapor deposition, allowing for controllable structure. The process of this invention is simple, reliable, and reproducible. The resulting SiC / SiO2 / C multi-component composite nanowire thin film exhibits high purity, controllable composition, a large aspect ratio, and uniform morphology and size.

[0027] The SiC / SiO2 / C ternary composite nanowire thin film prepared in this invention has a SiC core. NWs The composition ratio of the intermediate SiO2 phase and the outer shell C layer can be adjusted. On the one hand, the dielectric constant and impedance matching can be controlled. On the other hand, the multilayer core-shell structure can promote interface polarization and improve the microwave loss capability of the material.

[0028] The SiC / SiO2 / C ternary composite nanowire thin film prepared by this invention exhibits excellent microwave absorption performance, with advantages such as thin thickness, light weight, wide absorption frequency band, and high temperature resistance, and has broad application prospects in the field of microwave absorption.

[0029] This invention relates to self-supporting SiC structures NWs Based on the membrane, and combining the excellent properties of hollow structures, SiC was designed. NWs Inside the tube, C serves as the outer shell of the SiC@C tube's centerline structure. By adjusting the component ratio and void structure, complementary functions and simultaneous improvement of multiple properties can be achieved.

[0030] The SiC prepared by this invention NWs With a large aspect ratio, they can intertwine or overlap to form a network structure with good continuity, thereby self-assembling into a self-supporting membrane with certain mechanical properties. The process is simple, the parameters are easy to control, no metal catalyst impurities are introduced, the cost is low, it is easy to achieve large-scale production, and it has good economic benefits.

[0031] The present invention prepares a SiC@C nanowire thin film material with a tube-in-line structure, SiC NWs The microstructure and porosity of the nanowires can be controlled by adjusting the oxidation time and temperature. The outer shell C layer is prepared by chemical vapor deposition, which has good process stability and controllable C layer structure. A tube-in-line structure SiC@C nanowire thin film can be obtained through simple heat treatment. The process of this invention is simple, the parameters are easy to control, the equipment requirements are low, and the reliability and repeatability are good. The prepared tube-in-line structure SiC@C nanowire thin film has stable structure, high purity, large aspect ratio, and controllable morphology and size.

[0032] This invention prepares a SiC@C nanowire thin film with a tube-center structure, which is structurally stable and has controllable composition. The material prepared by this invention can be used as a lightweight and high-strength microwave absorbing material, and can also be used as a nano-conductive framework for supercapacitors, showing broad application prospects in electromagnetic absorption and supercapacitors. Attached Figure Description

[0033] Figure 1 SiC NWs A photograph of the actual thin film.

[0034] Figure 2 The image shows the X-ray diffraction pattern of the SiC / SiO2 / C multi-component composite nanowire thin film synthesized in Example 1.

[0035] Figure 3 The images show scanning electron microscope (SEM) images, transmission electron microscope (TEM) images, and surface scan images of the SiC / SiO2 / C multi-component composite nanowire thin film synthesized in Example 1.

[0036] Figure 4 The image shows a three-dimensional reflection loss diagram of the SiC / SiO2 / C multi-component composite nanowire thin film synthesized in Example 1.

[0037] Figure 5 The image shows the X-ray diffraction pattern of the SiC@C nanowire thin film with a tube-in-line structure synthesized in Example 1.

[0038] Figure 6 This is a scanning electron microscope image of the SiC@C nanowire thin film with a tube-in-line structure synthesized in Example 1.

[0039] Figure 7 The images show transmission electron microscopy (TEM) images and corresponding surface scans of the SiC@C nanowire thin films with a tube-in-line structure synthesized in Example 1.

[0040] Figure 8 This is a three-dimensional diagram of the reflection loss of the SiC@C nanowire thin film with a tube-in-line structure synthesized in Example 1.

[0041] Figure 9 The electrochemical performance analysis diagrams for the SiC@C nanowire thin film with a tube-in-line structure synthesized in Example 1 are as follows: (a) CV curves at different scan rates; (b) GCD curves at different current densities. Detailed Implementation

[0042] To enable those skilled in the art to better understand and implement the technical solutions of the present invention, the present invention will be further described below in conjunction with specific embodiments and accompanying drawings. However, the embodiments described are not intended to limit the present invention.

[0043] The first aspect of the present invention provides a silicon carbide-based ternary composite nanowire thin film, comprising ternary composite nanowires intertwined or overlapping to form a network structure;

[0044] The ternary composite nanowires include silicon carbide nanowires (SiC). NWs The silicon carbide nanowires are coated with a silicon dioxide (SiO2) layer and a carbon (C) layer.

[0045] The silicon carbide nanowires have a diameter of 30-500 nm; the silicon dioxide layer has a thickness of 10-250 nm; and the carbon layer has a thickness of 5-150 nm.

[0046] The second aspect of the present invention provides a silicon carbide-based binary composite nanowire thin film, which is prepared by removing a silicon dioxide layer from the aforementioned silicon carbide-based ternary composite nanowire thin film; the silicon carbide-based binary composite nanowire thin film comprises a network structure formed by intertwined or overlapping binary composite nanowires.

[0047] The binary composite nanowire film includes carbon nanotubes and silicon carbide nanowires inserted within the carbon nanotubes.

[0048] It should be noted that the binary composite nanowire thin film is a SiC@C nanowire thin film with a tube-in-line structure.

[0049] That is, a network structure formed by intertwined or overlapping SiC@C nanowires; the SiC@C nanowires include carbon nanotubes and SiC nanowires within the carbon nanotubes.

[0050] This invention is mainly based on SiC NWs They intertwine or overlap to form a network structure with good continuity in their SiC. NWs A C-layer structure is prepared on the surface to form SiC@C nanowires with a tube-center structure.

[0051] The carbon nanotubes have a wall thickness of 5-150 nm; the silicon carbide nanowires have a diameter of 30-500 nm; and the gap between the carbon nanotubes and the silicon carbide nanowires is 10-250 nm.

[0052] A third aspect of this invention provides a method for preparing a silicon carbide-based ternary composite nanowire thin film, comprising the following steps:

[0053] SiC NWs The film was subjected to oxidation treatment in an air atmosphere to obtain a SiC / SiO2 nanowire film.

[0054] The SiC / SiO2 nanowire film is placed in a deposition furnace, and argon gas is introduced at a rate of 1.5–2.5 L / min. The temperature is raised to 950–1100 °C at a rate of 4–6 °C / min. Then, methane is introduced at a rate of 0.6–1.2 L / min, and the temperature is maintained for 5–60 min to obtain a ternary composite nanowire film based on silicon carbide, referred to as SiC / SiO2 / C nanowire film.

[0055] Wherein, the SiC NWs The thin film is prepared according to the following steps:

[0056] Weigh a certain amount of glucose, silicon dioxide and sodium salt powder, grind them to make them evenly mixed, and then pass them through a 100-mesh sieve. Spread the sieved powder evenly into a graphite crucible.

[0057] A graphite crucible containing the mixed powder is held at 1400–1700℃ for 1–4 hours under an inert gas atmosphere to obtain SiC. NWs film.

[0058] Specifically, the molar ratio of glucose, silicon dioxide and sodium salt is 1:(1.2-4.5):(1.8-5.4); the sodium salt includes sodium chloride or sodium fluoride.

[0059] A fourth aspect of this invention provides a method for preparing a silicon carbide-based binary composite nanowire thin film, comprising the following steps:

[0060] The ternary composite nanowire film was heated at 1300–1600 °C for 1–4 h under inert gas protection to obtain a silicon carbide-based binary composite nanowire film, abbreviated as SiC@C nanowire film.

[0061] Among them, when the ternary composite nanowire film is heat-treated under the protection of an inert gas, the cooling rate is 3-5℃ / min.

[0062] The fifth aspect of this invention provides an application of silicon carbide-based ternary composite nanowire thin films in electromagnetic dissipation.

[0063] The sixth aspect of this invention provides an application of silicon carbide-based binary composite nanowire thin films in electromagnetic dissipation and supercapacitors.

[0064] In one embodiment, a method for preparing a silicon carbide-based multi-component composite nanowire thin film includes the following steps:

[0065] Step 1: Weigh a certain amount of glucose (C6H) 12 O6), silicon dioxide (SiO2), and sodium chloride (NaCl) powders are ground in a ceramic mortar until they are uniformly mixed. The mixed powder is then sieved through a 100-mesh sieve, and the sieved powder is evenly spread into a graphite crucible.

[0066] Step 2: Place the graphite crucible containing the mixed powder from Step 1 into a horizontal tube resistance furnace for heat treatment, and introduce inert argon gas as a protective gas. Hold at 1400–1700℃ for 1–4 hours, with a heating and cooling rate of 3–6℃ / min. After cooling to room temperature, remove the graphite crucible to obtain SiC. NWs film.

[0067] Step 3: Place SiC NWs The film was heat-treated in air at a rate of 4–6 °C / min. After being taken out at room temperature, the SiC / SiO2 nanowire film was obtained.

[0068] Step 4: Place the SiC / SiO2 nanowire film in a deposition furnace, introduce argon gas at a rate of 1.5-2.5 L / min, raise the temperature to 950-1100℃ at a rate of 4-6℃ / min, then introduce methane at a rate of 0.6-1.2 L / min, hold the temperature for a period of time, then stop introducing methane and close the deposition furnace. Cool the furnace to obtain the SiC / SiO2 / C nanowire film, which is the SiC / SiO2 / C ternary composite nanowire film.

[0069] Step 5: Place the SiC / SiO2 / C nanowire film in an alumina boat, put it in a horizontal tube furnace, and then introduce inert argon gas as a protective gas. After cooling to room temperature at a rate of 3-5℃ / min, remove the boat to obtain the SiC@C binary composite nanowire film with a tube-in-line structure.

[0070] The mixed powder C6H in step 1 12 The molar ratio of O6:SiO2:NaCl is 1:(1.2~4.5):(1.8~5.4).

[0071] The NaCl in step 1 can be replaced by NaF.

[0072] The oxidation temperature in step 3 is 1000–1200℃, and the holding time is 0.5–3 hours.

[0073] The heat preservation time in step 4 is 5 to 60 minutes.

[0074] The heat treatment temperature in step 5 is 1300–1600℃, and the holding time is 1–4 hours.

[0075] It should be noted that, unless otherwise specified, the experimental methods used in this invention are all conventional methods; and the reagents and materials used, unless otherwise specified, are all commercially available.

[0076] Example 1

[0077] Step 1: According to the molar ratio C6H 12 Weigh the raw materials (O6:SiO2:NaCl = 1:2.5:4.2) and grind them in a ceramic mortar until they are evenly mixed. Pass the mixed powder through a 100-mesh sieve and evenly spread the sieved powder into a graphite crucible.

[0078] Step 2: Place the graphite crucible containing the mixed powder from Step 1 into a horizontal tube furnace, then introduce argon gas as a protective gas, and heat to 1500℃ at a rate of 5℃ / min, holding at that temperature for 3 hours. After cooling to room temperature at a rate of 6℃ / min, remove the graphite crucible to obtain SiC. NWs Thin film, see Figure 1 As shown, SiC NWs A photograph of the actual thin film.

[0079] Step 3: Place SiC NWs The thin film was placed in an alumina boat and then placed in a horizontal tube furnace. Under air atmosphere, the temperature was increased to 1050℃ at a rate of 6℃ / min and held for 0.5h. After cooling to room temperature at a rate of 5℃ / min, the boat was removed to obtain the SiC / SiO2 coaxial nanowire thin film.

[0080] Step 4: Place the SiC / SiO2 coaxial nanowire film in a deposition furnace, introduce argon gas at a rate of 1.6 L / min, raise the temperature to 1100℃ at a rate of 6℃ / min, then introduce methane at a rate of 1.0 L / min, hold for 30 min, then stop introducing methane and turn off the deposition furnace. Cool with the furnace to obtain the SiC / SiO2 / C nanowire film, which is the SiC / SiO2 / C ternary composite nanowire film.

[0081] Step 5: Place the SiC / SiO2 / C nanowire film in an alumina boat, then place it in a horizontal tube furnace. Argon gas is introduced as a protective gas, and the temperature is raised to 1400℃ at a rate of 4℃ / min and held for 3 hours. After cooling to room temperature at a rate of 5℃ / min, the boat is removed to obtain the SiC@C nanowire film with a tube-in-line structure, which is the SiC@C binary composite nanowire film.

[0082] A SiC / SiO2 / C ternary composite nanowire thin film was successfully prepared using Example 1. Its X-ray diffraction pattern is shown below. Figure 2 Scanning electron microscope (SEM) images, transmission electron microscope (TEM) images, and surface scan images are shown in [reference needed]. Figure 3 The SiC / SiO2 / C nanowires exhibit a distinct multilayered core-shell structure, in which SiC... NWThe diameter is approximately 140 nm, the length is approximately tens of micrometers, the thickness of the middle SiO2 layer is approximately 115 nm, and the thickness of the C shell is approximately 30 nm. XRD results show that it has high purity and is free of other impurities. The three-dimensional reflection loss diagram of the core-shell structured SiC / SiO2 / C nanowire thin film absorbing material prepared in Example 1 is shown below. Figure 4 As shown, at a frequency of 9.20 GHz, the maximum reflection loss is -46.75 dB; and when the thickness is 2 mm, the bandwidth with a reflection loss of less than -10 dB is 5.12 GHz.

[0083] A SiC@C nanowire thin film with a tube-in-the-line structure was successfully prepared using Example 1. Its X-ray diffraction pattern is shown below. Figure 5 Scanning electron microscope image (see) Figure 6 Transmission electron microscope images and surface scans are shown in [reference]. Figure 7 The SiC@C exhibits a distinct centerline structure, where SiC... NW The diameter is approximately 140 nm, the length is approximately tens of micrometers, the thickness of the C-shell is approximately 35 nm, and the XRD results show that the purity is high, with no impurities or residual SiO2.

[0084] The three-dimensional reflection loss diagram of the SiC@C nanowire thin film material with a tube-center structure obtained in Example 1 is shown below. Figure 8 As shown in the figure, the maximum reflection loss of this composite material at a frequency of 13.52 GHz is [value missing]. Furthermore, when the thickness is 2.5mm, its reflection loss is less than With a bandwidth of 4.64 GHz, it exhibits excellent wave absorption performance. Figure 9 (a) shows the CV curves of the SiC@C nanowire thin film electrode with a tube-in-the-line structure at different scan rates. As the scan rate increases from 10 to 100 mV / s... -1 The current density and the area under the CV curve also increased accordingly, while the shape of the CV curve did not change significantly, indicating good electrochemical reversibility. Based on the GCD curve, the capacitance of SiC@C at a current density of 1 A / g can be calculated to be 15.9 mAh / g.

[0085] Example 2

[0086] Step 1: According to the molar ratio C6H 12 Weigh the raw materials (O6:SiO2:NaF = 1:3.6:1.8) and grind them in a ceramic mortar until they are evenly mixed. Pass the mixed powder through a 100-mesh sieve and evenly spread the sieved powder into a graphite crucible.

[0087] Step 2: Place the graphite crucible containing the mixed powder from Step 1 into a horizontal tube furnace, then introduce argon gas as a protective gas, and heat to 1700℃ at a rate of 5℃ / min, holding at that temperature for 2 hours. After cooling to room temperature at a rate of 4℃ / min, remove the graphite crucible to obtain SiC. NWs film.

[0088] Step 3: Place SiC NWs The thin film was placed in an alumina boat and then placed in a horizontal tube furnace. Under air atmosphere, the temperature was increased to 1200℃ at a rate of 5℃ / min and held for 1 hour. After cooling to room temperature at a rate of 6℃ / min, the boat was removed to obtain the SiC / SiO2 coaxial nanowire thin film.

[0089] Step 4: Place the SiC / SiO2 coaxial nanowire film in a deposition furnace, introduce argon gas at a rate of 2.4 L / min, raise the temperature to 1000℃ at a rate of 6℃ / min, then introduce methane at a rate of 0.8 L / min, hold for 40 min, then stop introducing methane and turn off the deposition furnace. Cool with the furnace to obtain the SiC / SiO2 / C nanowire film, which is the SiC / SiO2 / C ternary composite nanowire film.

[0090] Step 5: Place the SiC / SiO2 / C nanowire film in an alumina boat, then place it in a horizontal tubular resistance furnace. Argon gas is introduced as a protective gas, and the temperature is raised to 1500℃ at a rate of 4℃ / min and held for 2 hours. After cooling to room temperature at a rate of 5℃ / min, the boat is removed to obtain the SiC@C nanowire film with a tube-in-line structure, which is the SiC@C binary composite nanowire film.

[0091] Example 3

[0092] Step 1: According to the molar ratio C6H 12 Weigh the raw materials (O6:SiO2:NaF = 1:2:5) and grind them in a ceramic mortar until they are evenly mixed. Pass the mixed powder through a 100-mesh sieve and evenly spread the sieved powder into a graphite crucible.

[0093] Step 2: Place the graphite crucible containing the mixed powder from Step 1 into a horizontal tube furnace, then introduce argon gas as a protective gas, and heat to 1450℃ at a rate of 5℃ / min, holding at that temperature for 3 hours. After cooling to room temperature at a rate of 4℃ / min, remove the graphite crucible to obtain SiC. NWs film.

[0094] Step 3: Place SiC NWsThe thin film was placed in an alumina boat and then placed in a horizontal tube furnace. Under air atmosphere, the temperature was increased to 1150℃ at a rate of 5℃ / min and held for 2 hours. After cooling to room temperature at a rate of 6℃ / min, the boat was removed to obtain the SiC / SiO2 coaxial nanowire thin film.

[0095] Step 4: Place the SiC / SiO2 coaxial nanowire film in a deposition furnace, introduce argon gas at a rate of 2.4 L / min, raise the temperature to 1100℃ at a rate of 6℃ / min, then introduce methane at a rate of 0.8 L / min, hold for 20 min, stop introducing methane and close the deposition furnace, and cool with the furnace to obtain the SiC / SiO2 / C nanowire film, which is the SiC / SiO2 / C ternary composite nanowire film;

[0096] Step 5: Place the SiC / SiO2 / C nanowire film in an alumina boat, then place it in a horizontal tubular resistance furnace. Argon gas is introduced as a protective gas, and the temperature is raised to 1600℃ at a rate of 4℃ / min and held for 2 hours. After cooling to room temperature at a rate of 5℃ / min, the boat is removed to obtain the SiC@C nanowire film with a tube-in-line structure, which is the SiC@C binary composite nanowire film.

[0097] Comparative Example 1

[0098] Same as Example 1, except that:

[0099] Step 5: Place the SiC / SiO2 / C nanowire film in an alumina boat, then place it in a horizontal tube furnace. Argon gas is introduced as a protective gas, and the temperature is raised to 1100℃ at a rate of 4℃ / min and held for 2 hours. After cooling to room temperature at a rate of 5℃ / min, the boat is removed. The sample structure remains a SiC / SiO2 / C nanowire film; a tube-in-line structure is not obtained.

[0100] The mechanism of SiC@C binary composite nanowire film formation provided by the present invention is as follows: when the temperature reaches the melting point of glucose (146℃), glucose melts and coats the surface of NaCl and SiO2 particles; when the temperature continues to rise to 500℃, the glucose coated on the surface of the two particles is completely decomposed to obtain C with a higher specific surface area. During this process, the following reaction (1) occurs.

[0101] C6H 12 O6(s)→6C(s) + 6H2O(g) (1)

[0102] Subsequently, the temperature continued to rise to the melting point of sodium chloride, which is 801℃. NaCl melted to form molten salt, and SiO2 began to dissolve in the molten salt, resulting in the following reaction (2).

[0103] SiO2(s)→SiO2(l) (2)

[0104] Subsequently, C diffuses into the molten salt and reacts with SiO2 to generate SiO and CO gas, as shown in the following reaction (3). Once CO is formed, the reaction (4) may continue.

[0105] SiO2(l)+C(s)→SiO(g)+CO(g) (3)

[0106] SiO2(l)+CO(g)→SiO(g)+CO2(g) (4)

[0107] Because the C produced from glucose decomposition has a high specific surface area and high reactivity, it can react with SiO to form SiC nuclei, reaction (5). During the nucleation process, the formation of SiC nuclei will hinder the continued progress of the reaction due to the solid diffusion of C or the diffusion of SiO vapor molecules through SiC.

[0108] SiO(g)+2C(s)→SiC(s)+CO(g) (5)

[0109] Subsequently, the generated SiO and CO gases react further to form SiC crystals on the SiC core, reaction (6). Simultaneously, CO2 is immediately consumed via the Boudouard reaction (7). The obtained CO can, in turn, accelerate reaction (6).

[0110] SiO(g)+3CO(g)→SiC(s)+2CO2(g) (6)

[0111] CO2(g) + C(s) → 2CO(g) (7)

[0112] SiC NWs The growth process is mainly controlled by the reaction between SiO gas and CO gas, which allows the reaction to proceed rapidly in a short time, synthesizing a large number of nanowires. The nanowires intertwine to form a thin film. When the temperature continues to rise to the boiling point of NaCl, NaCl vapor is discharged with the gas flow, thus obtaining impurity-free SiC. NWs Thin film, see Figure 1 As shown. SiC NWs The thin film is obtained by oxidation treatment and chemical vapor deposition to obtain SiC / SiO2 / C nanowire thin film. After high temperature heat treatment, the core SiC layer and the outer shell C layer are structurally stable, while the SiO2 layer decomposes into SiO gas and volatilizes with the protective gas, leaving gaps to form SiC@C nanowires with a tube-in-line structure.

[0113] The impact of core-shell SiC / SiO2 / C nanowire films and tube-in-line SiC@C nanowire films on performance: On the one hand, the outer carbon nanotubes have high conductivity, allowing electrons to move freely on the surface and jump to adjacent nanowires, forming rapid electron migration paths and generating a three-dimensional conductive network, which leads to increased conductivity losses. Carbon nanotubes generally contain dangling bonds, lattice defects, and polar functional groups. Under the influence of an external electromagnetic field, these defects and polar functional groups act as dipole centers, resulting in dynamic separation of positive and negative charge centers. During this process, some electromagnetic energy is consumed, i.e., dipole polarization occurs. On the other hand, impedance matching is a prerequisite for microwave absorption. Impedance matching requires the input impedance Zin and the free-space impedance Z0 to be close. According to microwave transmission line theory, the closer Zin is to 1, i.e., the closer / Zin-1 / is to 0, the better the impedance matching. For core-shell structured SiC / SiO2 / C nanowire films, SiO2, as a transparent intermediate phase, has an adjustable thickness, which can better improve impedance matching and allow more electromagnetic waves to enter the absorbing material. Simultaneously, the SiC / SiO2 / C nanowire film possesses two binary composite interfaces. The difference in electronegativity of the components at the interface leads to the separation of positive and negative charges, generating stronger interfacial polarization. Furthermore, the core-shell structure effectively increases the contact area between the components, enhancing interfacial polarization and effectively improving dielectric loss. For tube-in-line structured SiC@C nanowire films, there are tunable gaps between the SiC core and the carbon nanotubes. These gaps act as impedance matching media, balancing the impedance of air and SiC@C. In addition, these gaps provide numerous microwave multiple reflection and scattering points, which is beneficial for microwave attenuation as the propagation path increases.

[0114] This invention describes preferred embodiments and their effects. However, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to include both the preferred embodiments and all changes and modifications falling within the scope of this invention.

[0115] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A ternary composite nanowire thin film based on silicon carbide, characterized in that, This includes a network structure formed by intertwined or overlapping ternary composite nanowires; The ternary composite nanowire includes silicon carbide nanowires, a silicon dioxide layer covering the surface of the silicon carbide nanowires, and a carbon layer covering the surface of the silicon dioxide layer. The silicon carbide nanowires have a diameter of 30-500 nm; the silicon dioxide layer has a thickness of 10-250 nm; and the carbon layer has a thickness of 5-150 nm. The silicon carbide-based ternary composite nanowire thin film is prepared according to the following steps: Silicon carbide nanowire films were oxidized in air to obtain SiC / SiO2 nanowire films. The SiC / SiO2 nanowire film was placed in a deposition furnace, and argon gas was introduced at a rate of 1.5~2.5 L / min. The temperature was increased to 950~1100℃ at a rate of 4~6℃ / min. Then, methane was introduced at a rate of 0.6~1.2 L / min, and the temperature was maintained for 5~60 min to obtain the silicon carbide-based ternary composite nanowire film. The silicon carbide nanowire film was prepared according to the following steps: Weigh a certain amount of glucose, silicon dioxide and sodium salt powder, grind them to make them evenly mixed, and then pass them through a 100-mesh sieve. Spread the sieved powder evenly into a graphite crucible. A graphite crucible containing the mixed powder is kept at 1400~1700℃ for 1~4h under the protection of an inert gas to obtain a silicon carbide nanowire film. The molar ratio of glucose, silicon dioxide, and sodium salt is 1:(1.2~4.5):(1.8~5.4). The sodium salt includes sodium chloride or sodium fluoride; The oxidation treatment is to remove SiC NWs The film is placed in an air atmosphere and kept at 1000~1200℃ for 0.5~3 hours.

2. A binary composite nanowire thin film based on silicon carbide, characterized in that, The silicon carbide-based ternary composite nanowire film of claim 1 is prepared by removing the silicon dioxide layer; the silicon carbide-based binary composite nanowire film comprises a network structure formed by intertwined or overlapping binary composite nanowires. The binary composite nanowire film includes carbon nanotubes and silicon carbide nanowires inserted within the carbon nanotubes.

3. The silicon carbide-based binary composite nanowire thin film according to claim 2, characterized in that, The carbon nanotube has a wall thickness of 5-150 nm; the silicon carbide nanowire has a diameter of 30-500 nm; and the gap between the carbon nanotube and the silicon carbide nanowire is 10-250 nm.

4. A method for preparing a silicon carbide-based ternary composite nanowire thin film as described in claim 1, characterized in that, Includes the following steps: Silicon carbide nanowire films were oxidized in air to obtain SiC / SiO2 nanowire films. The SiC / SiO2 nanowire film was placed in a deposition furnace, and argon gas was introduced at a rate of 1.5~2.5 L / min. The temperature was increased to 950~1100℃ at a rate of 4~6℃ / min. Then, methane was introduced at a rate of 0.6~1.2 L / min, and the temperature was maintained for 5~60 min to obtain the silicon carbide-based ternary composite nanowire film. The silicon carbide nanowire film was prepared according to the following steps: Weigh a certain amount of glucose, silicon dioxide and sodium salt powder, grind them to make them evenly mixed, and then pass them through a 100-mesh sieve. Spread the sieved powder evenly into a graphite crucible. A graphite crucible containing the mixed powder is kept at 1400~1700℃ for 1~4h under the protection of an inert gas to obtain a silicon carbide nanowire film. The molar ratio of glucose, silicon dioxide, and sodium salt is 1:(1.2~4.5):(1.8~5.4). The sodium salt includes sodium chloride or sodium fluoride; The oxidation treatment is to remove SiC NWs The film is placed in an air atmosphere and kept at 1000~1200℃ for 0.5~3 hours.

5. A method for preparing a silicon carbide-based binary composite nanowire thin film as described in claim 2 or 3, characterized in that, Includes the following steps: The ternary composite nanowire film was heated at 1300~1600℃ for 1~4h under the protection of an inert gas to obtain a silicon carbide-based binary composite nanowire film. Among them, when the ternary composite nanowire film is heat-treated under the protection of an inert gas, the cooling rate is 3~5℃ / min.

6. The application of the silicon carbide-based ternary composite nanowire thin film as described in claim 1 in electromagnetic dissipation and supercapacitors.

7. The application of the silicon carbide-based binary composite nanowire thin film as described in claim 2 or 3 in electromagnetic dissipation and supercapacitors.

Citation Information

Patent Citations

  • Surface-modified SiC nano wire, preparation method and applications thereof

    CN105733309A

  • Preparation method of silicon carbide nano-wire thin film material

    CN108046266A

  • Wave-absorbing and heat-insulating integrated composite material and preparation method thereof

    CN116396079A